Blood CD4+CD45RO+CXCR5+ T cells are decreased but partially functional in signal transducer and activator of transcription 3 deficiency - Mazerolles, Fabienne; Picard, Capucine; Kracker, Sven; Fischer, Alain; Durandy, Anne (Journal of allergy and clinical immunology, 2013)
The generation of high-affinity antibodies requires the presence of a population of CD4+ T cells (follicular TH [TFH] cells) in the lymph node follicles. These cells differ from TH1, TH2, and TH17 effector cells in that they strongly express activation markers and the chemokine receptor CXCR5 and secrete large amounts of IL-21 and CXCL13. Small numbers of nonactivated CD4+CD45RO+CXCR5+ T cells are also found in the blood. We sought to obtain in vitro a population close to the TFH cells and to study the presence of this cell population among patients with autosomal dominant hyper-IgE syndrome carrying heterozygous signal transducer and activator of transcription 3 (STAT3) mutations that impair the IL-21 signaling required for B-cell differentiation. CD4+CD45RO+CXCR5+ T cells were isolated from blood and activated by CD3/T-cell receptor. We found that CD4+CD45RO+CXCR5+ activated T cells corresponding to circulating bona fide memory TFH cells and that STAT3-deficient patients have abnormally low numbers of “TFH-like” blood T cells. However, STAT3-deficient TFH cells have much the same phenotypic and functional characteristics as TFH cells from healthy control subjects. The ability of STAT3-deficient TFH cells to produce IL-21 on CD28/T-cell receptor activation and to proliferate did not differ from that observed for control TFH cells in vitro. Although the STAT3-deficient TFH cells were also able to help control B cells to produce IgG and IgA, induction of IgG production by naive B cells was impaired. Heterozygous mutations in STAT3 lead to reduced numbers of circulating TFH-like cells, a finding that might account (at least in part) for the observed defect in antibody production.